Impact of surgical innovation on tissue repair in the surgical patient. Issue 2 (January 2015) - Tevlin, R.; Atashroo, D.; Duscher, D.; Mc Ardle, A.; Gurtner, G. C.; Wan, D. C.; Longaker, M. T.
<x xml:space="preserve">Abstract</x> Background Throughout history, surgeons have been prolific innovators, which is hardly surprising as most surgeons innovate daily, tailoring their intervention to the intrinsic uniqueness of each operation, each patient and each disease. Innovation can be defined as the application of better solutions that meet new requirements, unarticulated needs or existing market needs. In the past two decades, surgical innovation has significantly improved patient outcomes, complication rates and length of hospital stay. There is one key area that has great potential to change the face of surgical practice and which is still in its infancy: the realm of regenerative medicine and tissue engineering. Methods A literature review was performed using PubMed; peer‐reviewed publications were screened for relevance in order to identify key surgical innovations influencing regenerative medicine, with a focus on osseous, cutaneous and soft tissue reconstruction. Results This review describes recent advances in regenerative medicine, documenting key innovations in osseous, cutaneous and soft tissue regeneration that have brought regenerative medicine to the forefront of the surgical imagination. Conclusion Surgical innovation in the emerging field of regenerative medicine has the ability to make a major impact on surgery on a daily basis.